Study of PAPR reduction methods in OFDM systems - Mohammady, Somayeh; Mohd Sidek, Roslina; Varahram, Pooria; Hamidon, Mohd Nizar; Sulaiman, Nasri (IEEE, 2011)
High PAPR is the main drawback of OFDM systems. DSI method, PTS method and SLM method are three of the most promising techniques to reduce PAPR. This Work studies these methods and there is a comparison between their performances.